Involvement of IRAKs and TRAFs in anti-β2GPI/β2GPI-induced tissue factor expression in THP-1 cells - Xu, Guoying; Wen, Haiping; Hong, Zhou; Guo, Donglin; Zhou, Fang; Chen, Dongdong; Xie, Hongxiang; Wang, Ting; Wang, Haibo (Thrombosis and Haemostasis, 2011)
Our previous study has shown that Toll-like receptor 4 (TLR4) and its signalling pathway contribute to anti-β2-glycoprotein I/β2-glycoprotein I (anti-β2GPI/β2GPI)-induced tissue factor (TF) expression in human acute monocytic leukaemia cell line THP-1 and annexin A2 (ANX2) is involved in this pathway. However, its downstream molecules have not been well explored. In this study, we have established that interleukin-1 receptor-associated kinases (IRAKs) and tumour necrosis factor receptor-associated factors (TRAFs) are crucial downstream molecules of anti-β2GPI/β2GPI-induced TLR4 signaling pathway in THP-1 cells and explored the potential mechanisms of their self-regulation. Treatment of THP-1 cells with anti-β2GPI/β2GPI complex induced IRAKs and TRAFs expression and activation. Anti-β2GPI/β2GPI complex firstly induced expression of IRAK4 and IRAK1, then IRAK1 phosphorylation and last IRAK3 upregulation. In addition, anti-β2GPI/β2GPI complex simultaneously and acutely enhanced mRNA levels of TRAF6, TRAF4 and zinc finger protein A20 (A20), while chronically increased A20 protein level. Moreover, anti-β2GPI/β2GPI complex-induced IRAKs and TRAFs expression and activation were attenuated by knockdown of ANX2 by infection with ANX2-specific RNA interference lentiviruses (LV-RNAi-ANX2) or by treatment with paclitaxel, which inhibits TLR4 as an antagonist of myeloid differentiation protein 2 (MD-2) ligand. Furthermore, both IRAK1/4 inhibitor and a specific proteasome inhibitor MG-132 could attenuate TRAFs expression as well as TF expression induced by anti-β2GPI/β2GPI complex. In conclusion, our results indicate that IRAKs and TRAFs play important roles in anti-β2GPI/β2GPI-stimulated TLR4/TF signaling pathway in THP-1 cells and contribute to the pathological processes of antiphospholipid syndrome (APS).
Keywords: Anti-β2-glycoprotein I antibodies; β2-glycoprotein I; IRAKs; TRAFs; tissue factor